Do only rational humans possess dignity? - Ibañez, Franklin; Orozco, Richard (Con-Textos Kantianos. International Journal of Philosophy, 2025)
Kantian moral theory remains, directly or indirectly, the one that offers the strongest support for the notion of dignity, the cornerstone of contemporary moral and legal systems. Kant asserts that dignity belongs to all human beings as ends in themselves. However, many of the arguments he presents seem directly dedicated to justifying the dignity of only "rational subjects." From this, it could be deduced that perhaps not all human beings fit the bill, as some seem to lack rationality: specifically, those with radical cognitive disabilities. This article explores this problem in Kantian texts to propose that, ultimately, all humans possess dignity insofar as they are part of the unique moral species, or the one addressed by practical reason.